Assessing accrual accounting reform in Greek public hospitals: An empirical investigation - Nikolaos Eriotis; Filippos Stamatiadis; Dimitrios Vasiliou (International Journal of Economic Sciences and Applied Research, 2011)
During the last decades, several countries worldwide have introduced financial management reforms, as an important part of the New Public Management (NPM) initiative at one or more levels of government sector, by either replacing or transforming their traditional budgetary cash accounting systems towards a business-like accrual accounting concept. Following the example of this upcoming managerial trend, the Greek government introduced in 2003 the accrual basis accounting into public hospitals, as the hospital sector is one of the areas where NPM reforms have been introduced in search of higher efficiency, effectiveness and economy in service production. The purpose of this paper is twofold. The first goal is to provide an overview of the government sector reform initiatives in Greece and to present empirical evidence regarding the adoption level of the accrual basis accounting standards in the Greek public Health sector. The second goal of the research is to investigate the impact of a range of potentially contingent factors on hospitals compliance with the accrual financial and cost accounting reform. The present analysis is based on the results of an empirical survey that took place during 2009. For the purposes of this survey, a structured questionnaire was prepared and sent to the Chief Financial Officers (CFOs) of 132 Greek public hospitals. In particular, a linear regression model analysis was used to examine the cross-sectional differences on a number of explanatory and implementation factors of the accounting reform adoption level. The empirical evidence reveals that the level of accrual and especially cost accounting adoption in Greek public hospitals is realized only to a limited extent. In particular, results show that the level of reform adoption is positively related to IT quality, reform related training, education level of accounting staff, and professional consultants' support. However, no significant relationship was found between the level of reform adoption and hospital size, reform implementation cost, CEO educational background, experience effect, and absence of management-physicians conflict relationship. The main contribution of this study is the empirical evidence it provides on the approaches and processes used by the Government of Greece to implement accrual financial and cost accounting systems in the Greek National Health System (GNHS) and the role certain human, organizational and situational factors played in such implementations for enhancing researchers' and managers' understanding of major implementation processes and challenges as well as helping them refine models of effective implementation process and improve systems and processes on similar future projects.
Keywords: M4; M48; 330; accrual accounting; public sector accounting; compliance; public hospitals; contingency factors